Anticipated discrimination in daily life: Predictors, stress appraisals, and responses - Lydia Q. Ong; Megan W. Wolk; Anthony L. Burrow; Monika Lohani; Patrick L. Hill; Nancy L. Sin (PLoS ONE, 2026)
A large body of literature details the deleterious effects of everyday discrimination on health, focusing on stress processes after discrimination occurs. In contrast, less work has investigated what occurs prior to encountering discrimination when a person expects it. Using a 10-day daily diary design, the current study examined predictors and outcomes of anticipated discrimination. Participants included 341 U.S. adults aged 19–74 years (29% racial minorities, 68% women). Multiple regression examined predictors of anticipated and reported discrimination. Further, two-level multilevel models evaluated anticipated discrimination predicting discrimination occurrence, appraisals, affect, and physical symptoms. Results showed that discrimination was anticipated on 21% of days; racial minorities and people with more prior exposure to discrimination anticipated more daily discrimination than White participants and those with lower prior exposure. People who anticipated discrimination more often than others reported more daily discrimination and perceived discrimination as more stressful but also perceived greater control over the events. They additionally had relatively larger upticks in physical symptoms on days when discrimination occurred—but no differences in discrimination-related affect—compared to people who anticipated discrimination less frequently. Within-persons, anticipating discrimination on a given day (versus not) was associated with greater likelihood of reporting discrimination occurred later that day and greater perceived stress severity, but no differences in perceived control, affect, or physical symptoms. In sum, anticipated discrimination was fairly common in daily life, and individual differences in anticipated discrimination were linked to more perceived daily discrimination, higher perceived stress severity, and more discrimination-related physical symptoms.